TYPICAL TASIKMALAYA TRADITION OF SEMANTIC ANALYSIS OF FIELDS OF MEANING - Vanessa Viviana Shodiq; Abdul Karim Amrullah; Eulis Siti Nurallawiah; Nisrina Farida Margana; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to describe the results of semantic meaning field analysis contained in the Tasikmalaya cash tradition. The research method used is a qualitative descriptive method using reading and note-taking techniques, namely reading from several sources and then recording the information contained in them. The research data carried out is a form of typical Tasikmalaya tradition which is categorized in the field of semantic meaning. The data source is the typical Tasikmalaya tradition obtained from reading both journals and printed books. The research results show that the field of meaning in typical Tasikmalaya traditions can be classified into 3 parts, namely traditions related to musical instruments consisting of the Lodong Gejlig, Terbang Gebrug, and Gondang traditions. Typical Tasikmalaya traditions related to belief consist of the Hajat Laut, Passoka, Hajat Sasih Ceremony, and Rarangken Paré. Apart from that, traditions related to an activity carried out by a group of people at an event or not, consist of the Nyapu Kabuyutan, Ngubek Balong, and Nincak Endog traditions.